ANALYSIS OF VIRTUAL COMMUNITIES IN TOURISM - DENCHEVA, Silvena (Ecoforum Journal, 2013)
Internet has changed the way companies interact with customers. Customers have become the active part of the communication with business. Virtual communities are the most popular implication of the usage of Internet into business world. The article presents the nature of virtual communities and how they are functioning in the hospitality industry. The web site of hotel Dobruzda-Dobrich has been analyzed regarding its Internet presence. Internet marketing strategy for improving its internet presence is presented in the paper.